Utilizing Group Investigation Techniques to Enhance Students’ Reading Comprehension Skills on Recount Text - Ledy Nur Lely; Welliam Hamer; Fathimah Zahroh (Journal of English Education Studies, 2020)
Recount text is one of the texts in writing which must be taught and stated in Junior High School curriculum. Some students felt that reading text is boring because the students tend to be very lazy to read the text, so that they are not interested in English lessons. The researchers used group investigation technique as one of alternatives in teaching and learning to develop the material and make students more active and interested in class. The objective of this research is to find out whether teaching using group investigation technique is able to develop the students’ reading in recount text at the eighth grade students of SMP Negeri 17 Kota Serang. The methodology of this research was a quantitative research method by using true experimental design. The study was carried out into two classes, Class VIII E as experimental class, and Class VIII C as control class. The results of the study showed that group investigation was able to develop students’ reading comprehension in recount text. Mean of posttest score of the experimental class (67.31) was higher than the control class (64.18). Based on the statistical analysis using t-test analysis, it showed the value of tcount ≥ ttable = 49.12 ≥ 1.99. It means that (Ha) was accepted and the (H0) was rejected. It can be concluded that group investigation is able to develop students’ reading comprehension in recount text at eighth grade students of SMP Negeri 17 Kota Serang.